Phytochemical Screening, Antimicrobial Properties and Pharmaceutical Applications of Tapinanthus globiferus Leaf Extract - Bong, Alang Michael; Benoit, Ngassoum Martin; Sohanang, Nodem; Danielle, Fotio Defo; Akah, Njong Vera (European Journal of Applied Sciences, 2024)
This study was carried out unveil the secondary metabolites of Tapinanthus globiferus leaves used in traditional medicine through meticulous phytochemical screening. The leaf extracts were obtained by methods of Soxhlet extraction and maceration using water and ethanol as solvents. The leaf extracts were used to carry out phytochemical screening, carry out some antimicrobial susceptibility tests and indicate some industrial applications of the plant extracts. The extract obtained by maceration in 95% ethanol gave a yield of 14.85% and extract tested positive flavonoids and other polyphenolic compounds. For extended qualitative analyses, the following secondary metabolites were identified; tannins, saponins, anthraquinones, reducing sugars, alkaloids and terpenoids. The phenolic compounds present give the extract antioxidant and antimicrobial properties. The antimicrobial susceptibility tests were done on three bacterial species (E. coli with 27.78% inhibition, Staphylococcus aureus 28.33%; Streptococci 23.33%) and a mold (C. albicans with a percentage inhibition of 26.67%). Results from microbiological analysis showed that the plant extracts could inhibit the proliferation of some pathogenic bacterial and fungal species. The minimum inhibitory concentration (MIC) of the plant extract was 15.63 mg/mL for both E. coli, S. aureus, and Streptococcus respectively while the MIC for C. albicans was 125 mg/mL. But the minimum bactericidal concentration (MBC) of the plant extract against the bacteria was 125 mg/mL while the minimum fungicidal concentration (MFC) of the plant extract against C. albicans was 250 mg/mL. The outcome of this research validates the use of this plant in traditional medicine and also validating the plausible application of Tapinanthus globiferus in pharmaceutical and cosmetic preparations for public health enhancement amongst others.